Histology core-specific evaluation of the European Society of Urogenital Radiology (ESUR) standardised scoring system of multiparametric magnetic resonance imaging (mpMRI) of the prostate - Kuru, Timur Hasan; Röthke, Matthias C.; Rieker, Philip; Roth, Wilfried; Fenchel, Michael Christian; Hohenfellner, Markus; Schlemmer, Heinz-Peter; Hadaschik, Boris (BJU international, 2013)
Objectives To evaluate the Prostate Imaging Reporting and Data System (PIRADS) in multiparametric magnetic resonance imaging (mpMRI) based on single cores and single-core histology. To calculate positive (PPV) and negative predictive values (NPV) of different modalities of mpMRI. Patients and Methods We performed MRI-targeted transrectal ultrasound-guided perineal prostate biopsies on 50 patients (mean age 66 years, mean PSA level of 9.9 ng/mL) with suspicion of prostate cancer. The biopsy trajectories of every core taken were documented in three dimensions (3D) in a 3D-prostate model. Every core was evaluated separately for prostate cancer and the performed biopsy trajectories were projected on mpMRI images. PIRADS scores of 1177 cores were then assessed by a histology ‘blinded’ uro-radiologist in T2-weighted (T2W), dynamic contrast-enhanced (DCE), diffusion-weighted imaging (DWI) and magnetic resonance spectroscopy (MRS). Results The PIRADS score was significantly higher in cores positive for cancer than in negative cores. There was a significant correlation between the PIRADS score and histopathology for every modality. Receiver operating characteristic (ROC) analysis showed excellent specificity for T2W (90% peripheral zone/97% transition zone) and DWI (98%/97%) images regardless of the prostate region observed. These numbers decreased for DCE (80%/93%) and MRS (76%/83%). All modalities had NPVs of 99%, if a PIRADS score threshold of 2 (for T2W, DCE, and MRS) or 3 (for DWI) was used. However, PPVs were low. Conclusions Our results show that PIRADS scoring is feasible for clinical routine and allows standardised reporting. PIRADS can be used as a decision-support system for targeting of suspicious lesions. mpMRI has a high NPV for prostate cancer and, thus, might be a valuable tool in the initial diagnostic evaluation.
Gesehen am 14.07.2021